Behavior of the extended spectral measure of a self-adjoint operator at infinity - Gorbachuk, V. I.; Gorbachuk, M. L. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the dependence of the rate of growth of the extended spectral measure of a self-adjoint operator at infinity on the order of singularity of the vector on which this measure is considered.